Silent Patent Ductus Arteriosus Aneurysm - Botta,Aline Medeiros (2002)
Ductus arteriosus aneurysm, a rare and potentially fatal condition, has been reported as a complication after surgical ductus arteriosus closure. Its spontaneous appearance as a septic complication, which was common in the presurgical and preantibiotic era, has been rarely reported in the contemporary literature. Persistence of silent ductus arteriosus in healthy children and adults is a frequent condition that currently has an increasing diagnostic possibility due to the availability of more accurate investigative methods, especially echocardiography. We report the case of a 1-year-old child, in whom no previous heart disease was known, who developed a giant aneurysm of the ductus arteriosus during a staphylococcal infection. This complication appeared after craniotomy for emptying an accidental subdural hematoma. This report associates the persistence of ductus arteriosus with a complication considered rare, which has a rapidly fatal evolution.